The Role of Indonesian Constitutional Law in Sustaining National Resilience Amid Global Challenges - Kennedy, Alexander (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study examines the role of Indonesian constitutional law in fostering national resilience amid evolving global challenges, including pandemics, climate change, and cyber threats. It aims to analyse how the 1945 Constitution supports national resilience and identify legal gaps that limit its effectiveness. The research also explores potential constitutional reforms to enhance Indonesia’s preparedness and response capacity to modern risks. Study Design/Methodology/Approach: This research employs a normative juridical approach, focusing on doctrinal analysis of legal texts to evaluate constitutional provisions, legislative frameworks, and judicial interpretations. Key legal instruments, such as the 1945 Constitution, national security laws, and disaster management regulations, are critically assessed. Comparative analysis with international constitutional models provides insights into best practices for integrating resilience-focused legal principles. Findings: The findings highlight Indonesia’s constitutional strengths, particularly its emphasis on sovereignty, human rights, social welfare, and governance stability. However, gaps remain, especially in addressing digital security, climate resilience, and transnational threats. The lack of explicit constitutional provisions on these issues, coupled with weak enforcement mechanisms, limits Indonesia’s ability to anticipate and respond effectively. This study recommends constitutional amendments to incorporate cyber resilience, climate change adaptation, and pandemic preparedness while strengthening judicial oversight and public participation in legal reforms. Originality/Value: This study contributes to academic and policy discourses by reinforcing the role of constitutional law in sustaining national resilience. It provides practical recommendations for constitutional reform, aligning Indonesia’s legal framework with global standards while addressing local vulnerabilities. By adopting a proactive, resilience-oriented legal approach, Indonesia can enhance its legal adaptability and governance stability in the face of emerging global challenges.